The value of colour doppler assessment of the uteroplacental circulation in predicting intrauterine growth restriction - Dhakar, Vimla; Naz, Sabiha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine growth restriction is a complication that arises due to decrease in uteroplacental blood flow during pregnancy. This decrease is associated with a pathological condition of spiral arteries thought to arise during placentation in first trimester of pregnancy. Thus, it might be possible to predict the development of these conditions by assessing uteroplacental blood flow in pregnancy with colour Doppler. The aim of the study was to assess the findings of Doppler data in predicting IUGR and finding the best predictors of IUGR in uterine and umbilical artery Doppler. Methods: In this prospective study, total of 100 women with high risk pregnancy attending Department of Obstetrics and Gynecology at Geetanjali Medical College and Hospital, Udaipur were subjected to uterine and umbilical artery Doppler Study. Women with high risk pregnancy between 26-32 weeks of gestation were studied with colour Doppler. This study was carried over a period of 1 year from 2015-2016. Results: Out of total 100 patients, 8 were found to have IUGR. Out of different parameters, Notch is the best indicator with high sensitivity and highest positive predictive value (PPV) of 50% followed by combination of parameter as it had the highest sensitivity of 62.5% for uterine artery Doppler. S/D Ratio is the best indicator with high sensitivity and highest positive predictive value (PPV) of 25% and 40% respectively followed by RI with highest sensitivity of 42.86% for umbilical artery Doppler. Conclusions: Value of Doppler assessment of uteroplacental circulation in predicting IUGR and is very useful in improving pregnancy outcome.